Effect of caffeic acid and caffeic acid phenethyl ester on murine osteosarcoma cells: regulation of the NADPH oxidase complex - Pagnan, Ana Lígia (2021)
Osteosarcoma is the most common type of bone cancer among children and adolescents. Metastasis for this cancer happens around 10-25% of the cases, increasing the mortality rate. The search for new therapeutic strategies has increased for phytochemicals due to their potential as antioxidants and anticancer properties. Studies have reported these properties on caffeic acid phenethyl ester (CAPE) and caffeic acid (CA). In this way, the present study aimed to analyze CAPE and CAs anticancer properties on UMR-106 murine osteosarcoma cells after 72 h of treatment. Cell viability was assessed using the MTT and violet crystal reduction assay, with inhibitory concentrations corresponding to 25 and 50% (IC25 and IC50) of 1.3 and 2.7 M for CAPE and 91.0 and 120.0 M for AC, respectively. In addition, a control cell line (MC3T3-E1) was also used for the viabilities assay. The number of apoptotic cells and proliferation rate were quantified by flow cytometry with ANEXIN V-FITC/DRAQ7 and CFSE, respectively and the cell migration behavior was evaluated by the Wound Healing assay. The quantification of reactive oxygen species (ROS) was performed by DCFH-DA fluorescence. NOX-2 and NOX-4 genes were analyzed by RT-qPCR. Data were analyzed by one-way ANOVA. Significant differences between groups were determined by Tukeys post-hoc test at P<0.05. Thus, the present study shows the potential anticancer properties of CAPE and highlights how a simple chemical modification can improve the pharmacological potency of a phytochemical in relation to its precursor CA. Our results showed that CAPE was more efficient and selective in reducing the viability of tumor cells, with significant differences, when compared to the control (P<0.05) and it was 44-fold (IC25) and 70-fold (IC50) more cytotoxic than CA. CAPE also induced apoptosis and decreased ROS generation, in addition to limiting cell migration. In summary, CAPE was more selective for tumor cells, preserving normal ones, suggesting its potential role as an anticancer drug.